Hypoglycemic Activity of Hydro-Acetonic and HydroMethanolic Leaf and Bark Extracts of Bauhinia rufescens Lam in Mice - Niang, Lahat; Seid Ali, Mahamat; Faye, Papa Guédel; Ayessou, Nicolas Cyrille; Cisse, Mady (European Scientific Journal, ESJ, 2023)
The purpose of this study was to determine the hypoglycaemic effects of leaf and bark extracts of Bauhinia rufescens Lam, used in traditional medicine for diabetes in Senegal. Phytochemical screening of hydromethanolic and hydro-acetonic extracts obtained from leaves and barks was carried out according to standard analytical methods. Experiments were carried out on normoglycemic and diabetic mice. These were obtained after the injection of a single dose of glucose (4 g/kg of body weight). The results showed that polyphenolic compounds, tannins, and flavonoids were the main phytochemical constituents of the extracts. Then the oral administration of the different extracts of Bauhinia rufescens Lam at doses of 500, 700, and 1000 mg/kg of body weight led to a significant reduction in blood sugar (p < 0.05), similar to the antidiabetic action of glibenclamide (10 mg/kg of body weight). Whatever the organ and the extraction solvent, the doses of 500 and 700 mg/kg of body weight induced dose-dependent hypoglycemia, just like glibenclamide. These results show that the metabolites revealed in the extracts could be responsible for their hypoglycemic effects. Thus, supported by a complete chemical study with a view to isolating the active substances responsible for the antidiabetic effect is possible. It will be allowed to formulate from a phytomedicine with potential for diabetes which makes possible their uses by populations for treatment of diabetes.